1978
DOI: 10.1207/s15327906mbr1304_3
|View full text |Cite
|
Sign up to set email alerts
|

The Use Of Analysis Of Covariance Structures For Comparing The Psychometric Properties Of Multiple Variables Across Populations

Abstract: It is common practice to assume that the dependent variables in differential prediction studies, and analysis of variance and co-variance designs are characterized by certain psychometric properties which are invariant across the subgroups of interest. More specifically, the accuracy of the results of such analyses depends on the assumption that the dependent variables are measuring the constructs in the same metrics with equivalent reliabilities across all subgroups. Systematic procedures are outlined for tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 0 publications
0
81
0
Order By: Relevance
“…The next higher level of invariance, 'measurement' or 'metric' invariance, assesses a necessary condition for equivalence of meaning. This level requires that the factor loadings between items and constructs are invariant across countries (Rock, Werts and Flaugher 1978). It is tested by restricting the factor loading of each item on its corresponding construct to be the same across countries.…”
Section: Testing Invariancementioning
confidence: 99%
“…The next higher level of invariance, 'measurement' or 'metric' invariance, assesses a necessary condition for equivalence of meaning. This level requires that the factor loadings between items and constructs are invariant across countries (Rock, Werts and Flaugher 1978). It is tested by restricting the factor loading of each item on its corresponding construct to be the same across countries.…”
Section: Testing Invariancementioning
confidence: 99%
“…One recommendation that emerges repeatedly in the comments on Schönemann's critique is that a model fitting approach, based on the theory of factorial invariance, should be favoured to Jensen's test in investigating B-W differences in IQ data (Horn, 1997;Millsap, 1997a;Gustafsson, 1992;Dolan, 1997). Confirmatory factor analysis has been applied to B-W differences in measures of cognitive abilities (law students' exam scores in the case of Rock, Werts, & Flaughter, 1978; children's WISC scores in the case of Gustafsson, 1992). However, these analyses have been limited to just one specific factor model.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that in order to meaningfully test for gender differences, any standardised instrument should produce the same or "invariant" factor structures for males and females (Rock, Werts, & Flaugher, 1978). Indeed, the present study revealed that the bifactor model with a general self-esteem factor and positive and negative grouping factors provided an adequate fit for both boys and girls, therefore permitting the comparison of RSES scores between girls and boys affected by parental imprisonment.…”
Section: Discussionmentioning
confidence: 60%